Importancia de la cosecha para mejorar la calidad y rendimiento en la extracción de aceite en el racimo de palma aceitera (Elaeis guineensis Jacq). - Almache Bajaña, Marck Anthony (2022)
The objective of this case study is to determine the importance of the harvest to improve the quality and yield in oil extraction in the oil palm (Elaeis guineensis Jacq) bunch. Through an exhaustive bibliographic review, where articles, documents, texts, books and web pages were collected, selected and analyzed that served to provide the theoretical bases of the subject to be treated. The harvesting process and the techniques used directly influence the quality and profitability of the palm crop. When a green fruit is harvested, the amount of oil decreases. If an overripe product is harvested, the oil is acidic. Identifying the right time to cut guarantees a better production with quality. It is important to carry out an adequate transport to minimize the loss of fruit. In addition, the quality of the oil decreases if it exceeds 24 hours of cut.